Carotene contents of processed meats blended with palm fats - Wan Rosli, W. I.; Babji, A.S.; Aminah, A.; Foo, S. P.; Abd Malik, O. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2004)
(beef burgers and chicken frankfurters) blended with palm fats was studied. Alpha-carotene and β-carotene decreased significantly (P<0.05) by 62-66% and 72-80% respectively in beef burgers where the fats were substituted with red palm fat (RPF35) and a mixture of red palm fat and palm fat (FB) when the meats were stored at -18oC for 6 month after cooking. Alpha-carotene lost by 53% and 33% while beta-carotene by 67% and 47%, respectively in raw beef burger where the fats were replaced with RPF35 and FB After storage for 6 months (-18oC). Alpha-carotene concentrations lost by 66% and 62%, respectively in beef burger substituted with RPF35 and FB during storage for 6 months at -18oC after cooking. Alpha-carotene in retorted chicken frankfurter (RC) substituted with RPF48 only lost 25% while oven-cooked chicken frankfurter (OC) containing RPF48 lost 61%. Beta-carotene was degraded faster compared to α-carotene in RC, OC and cooked beef burger indicating that the beef burger was more stable after cooking and storage. Even though OC, RC frankfurters and cooked beef burgers substituted with red palm fat showed the highest percent loss in β-carotene concentrations after storage, the value retained was still the highest (23.0, 42.0 and 23.8 μg/g, respectively). In summary, the effect of processing, cooking, frozen storage and the type of fats used could influence the stability of alpha- and beta-carotenes and their content in meat products.